Diversity among welfare states : comparative studies on welfare state adjustment in Nordic countries - Kautto, Mikko; Helsingin yliopisto. Sosiologian laitos (Research report / Stakes, ISSN 1236-0732, 2001)
Referat: Diversitet bland välfärdsstaterna.
Keywords: hyvinvointivaltio; muutos; sosiaalipolitiikka; yhteiskuntapolitiikka; Pohjoismaat